Analysis on the Susceptibility Genes in Two Chinese Pedigrees with Familial Parkinson's Disease. (19th July 2010) - Xu, Changshui; Xu, Jun; Zhang, Yanmin; Ma, Jianjun; Kawakami, Hideshi; Maruyama, Hirofumi; Kamada, Masaki
Abstract : Objective . To screen the susceptibility genes in Chinese pedigrees with early-onset familial Parkinson's disease (FPD). Methods . Fifty-one genomic DNA samples extracted from two Chinese pedigrees with FPD, the alpha-synuclein genes (SNCA), the leucine-rich repeat kinase 2(LRRK2), PINK1(PTEN-induced putative kinase 1), PARK7(Protein DJ1), PARK2(Parkinson juvenile disease protein 2), the glucocerebrosidase ( GBA ), and ATP(Ezrin-binding protein PACE-1), were sequenced by the use of polymerase chain reaction (PCR) technique. The gene dose of SNCA was checked. Results . There were only two missense mutations observed, respectively, at exon 5 of LRRK2 and exon 10 of PARK2, and both were enrolled in SNPs. Conclusion . No meaningful mutations could be detected, and other susceptibility genes should be detected in FDP patients in China.